2022
DOI: 10.3390/ani12162010
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and Metabolomics Analysis of the Ovaries of High and Low Egg Production Chickens

Abstract: Egg production is a pivotal indicator for evaluating the fertility of poultry, and the ovary is an essential organ for egg production and plays an indispensable role in poultry production and reproduction. In order to investigate different aspects of egg production mechanisms in different poultry, in this study we performed a metabolomic analysis of the transcriptomic combination of the ovaries of two chicken breeds, the high-production Ninghai indigenous chickens and the low-production Wuliangshan black-boned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Similar patterns emerged in the pituitary, thyroid, and ovarian stroma, where DEGs were predominantly enriched in the extracellular space. Among these, several DEGs, including SCG2, PRL ( Shiue et al, 2006 ), SHH ( Ye et al, 2019 ), FABP3, INHBB ( Huang et al, 2022 ), CCK ( Mu et al, 2021 ), etc., have been reported to be associated with laying performance. Furthermore, previous research on bulls has indicated that sperm from highly fertile bulls have high levels of extracellular space transcripts, which might be related to the bull's fertility ( Feugang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns emerged in the pituitary, thyroid, and ovarian stroma, where DEGs were predominantly enriched in the extracellular space. Among these, several DEGs, including SCG2, PRL ( Shiue et al, 2006 ), SHH ( Ye et al, 2019 ), FABP3, INHBB ( Huang et al, 2022 ), CCK ( Mu et al, 2021 ), etc., have been reported to be associated with laying performance. Furthermore, previous research on bulls has indicated that sperm from highly fertile bulls have high levels of extracellular space transcripts, which might be related to the bull's fertility ( Feugang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The positively selected DYNLL2 gene, apart from its role in immune response, was also found to be a regulator of chicken myogenesis, providing insights into breast muscle development in chickens and other birds (Li et al, 2022). VIPR2, one of the positively selected cAMP signaling pathway genes identified in domestic Japanese quails, has been implicated in the regulation of egg production as it has been associated with brooding behavior in chicken and geese (Luan et al, 2014;Huang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic analysis is concerned with investigating the entire range of small molecules (metabolites) found in biological samples and revealing metabolic pathways crucial for fertility, embryonic development, and reproductive health in chickens by characterizing the metabolites linked with reproductive activities. Metabolomics has revealed information on nutrient use, energy metabolism, and biomarkers in poultry reproduction [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic investigations can assist veterinarians and breeders in early diagnosis and the implementation of focused treatment methods by identifying the biomarkers linked to reproductive diseases or inadequate fertility [ 72 ]. Transcriptomic research, by deciphering the complex gene expression profiles associated with critical reproductive processes, provides the path for the identification of genetic markers, breeding program optimization, and improved reproductive outcomes in poultry production [ 13 , 73 ].…”
Section: Introductionmentioning
confidence: 99%